2021
DOI: 10.3892/etm.2021.10132
|View full text |Cite
|
Sign up to set email alerts
|

Anti‑inflammatory activities of Gardenia jasminoides extracts in retinal pigment epithelial cells and zebrafish embryos

Abstract: Age-related macular degeneration (AMD) is the most common cause of visual impairment in developed countries. Inflammation serves a critical role in the pathogenesis of AMD. Gardenia jasminoides is found in several regions of China and is traditionally used as an organic yellow dye but has also been widely used as a therapeutic agent in numerous diseases, including inflammation, depression, hepatic and vascular disorders, which may reflect the variability of functional compounds that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Gardenia is the first batch of medicinal and edible plant resources announced by the Ministry of Health in China. Gardenia extract has antioxidant, antibacterial [ 10 ], and immune-enhancing functions [ 11 , 12 ]. Ripe gardenia fruit, as a traditional medicinal material in China, protects the liver, promotes bile secretion, and benefits the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%
“…Gardenia is the first batch of medicinal and edible plant resources announced by the Ministry of Health in China. Gardenia extract has antioxidant, antibacterial [ 10 ], and immune-enhancing functions [ 11 , 12 ]. Ripe gardenia fruit, as a traditional medicinal material in China, protects the liver, promotes bile secretion, and benefits the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that GJ extracts have anti-inflammatory and antioxidant properties [26,27,33,34], and are effective against allergic inflammatory diseases such as asthma and atopic dermatitis [30,31]. Based on these findings, we investigated allergic inflammatory mediators, immune cells including eosinophils, and their underlying mechanisms to understand how GJW and GJE inhibit AR inflammation-like conditions in an ovalbumin-induced AR mouse model and in IL-4/IL-13-treated (i.e., inflammatory pathway-activated) HNEpCs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that GJ fruits have antipyretic, diuretic, and detoxifying effects, and are widely used as antiphlogistic, analgesic, and anti-inflammatory agents. Moreover, they have antiangiogenic, antidiabetic, anticancer, antioxidant, and anti-depressant properties while also improving sleep quality [25][26][27]. The major constituents of GJ include iridoid glycosides and their aglycones (genin) as well as bioactive compounds such as gardenoside, geniposide, genipin, and crocin [28,29].…”
Section: Introductionmentioning
confidence: 99%